Analisis Kelayakan Bisnis Usaha Kuliner “Nangkring Seblak” Menggunakan Analisis SWOT Berdasarkan Persepsi Konsumen - Indah Pangestu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of micro, small, and medium enterprises (MSMEs) in the culinary sector in Indonesia has shown significant growth, particularly in traditional food products packaged in modern ways, such as seblak. The high public interest in spicy food has encouraged the emergence of many similar businesses, resulting in increasingly fierce competition. This study aims to analyze the feasibility of the Nangkring Seblak business based on consumer perceptions and the business's internal and external conditions. The research method used was descriptive quantitative, with data collection through a survey using a Google Form questionnaire administered to 23 respondents. The data obtained were analyzed through respondent characteristics analysis, consumer perception analysis, and a SWOT analysis to formulate business development strategies. The results showed that the majority of respondents gave positive assessments of the taste quality, affordable prices, and menu innovation offered by Nangkring Seblak. The SWOT analysis revealed that the business's main strengths lie in consistent product quality and competitive pricing, while its main weaknesses are limited promotion and limited operational scale. Based on these analysis results, it can be concluded that the Nangkring Seblak business is feasible to operate and develop sustainably with the implementation of appropriate strategies.